2009
DOI: 10.1063/1.3130402
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent neutron diffraction study of phase separation at morphotropic phase boundary in (1−x)BiScO3–xPbTiO3

Abstract: We report the results of temperature-dependent neutron powder diffraction experiments on (1−x)BiScO3–xPbTiO3 (x=0.62, 0.64, and 0.66) within the morphotropic phase boundary. In all samples the monoclinic phase is found to coexist with the tetragonal phase below the ferroelectric transition temperature. The details of structural information demonstrate a delicate balance between the coexisting two phases for x=0.64. Such delicate balance is suggested to be sensitive to an external electric field, thus responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Certain compositions closer to phase boundaries have been shown to exhibit two or more phases in coexistence. [27][28][29] In such cases, it has been suggested that the motion of the interface separating these phases, or interphase boundary motion, may significantly affect the macroscopic properties time-resolved data is acquired stroboscopically and is synchronized with the cyclic electric field.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Certain compositions closer to phase boundaries have been shown to exhibit two or more phases in coexistence. [27][28][29] In such cases, it has been suggested that the motion of the interface separating these phases, or interphase boundary motion, may significantly affect the macroscopic properties time-resolved data is acquired stroboscopically and is synchronized with the cyclic electric field.…”
Section: 23mentioning
confidence: 99%
“…This additional Bragg scattering may be interpreted as the (002) R reflection of a rhombohedral phase 41 or, more recently, has been associated with the (002) M and (220) M reflections of a monoclinic phase (space group Cm). 29 Using the refined crystallographic data for the monoclinic phase of BS-64PT from Kim et al, …”
Section: B In Situ Neutron Diffraction Measurements: Quasi-static Elmentioning
confidence: 99%
“…The starting powders of Pb(CO 3 ), Bi 2 O 3 , TiO 2 and Sc 2 O 3 were stoichiometrically mixed and ball milled in ethanol for 12 h. After drying, the mixture was calcined at 760 °C for 5 h and ball milled for an additional 12 h. The calcined powder was then pressed into disk-shaped pellets and sintered in a closed crucible at 1100 °C for 1 h embedded in calcined powder of the same composition. An XRD pattern of the as-synthesized material confirmed the phase purity and coexistence of a tetragonal phase with a second polymorph, which is attributed to either a rhombohedral or monoclinic phase as stated in prior observations [1][2][3][4][5][6]. The grain size of the samples was approximately 1 µm from scanning electron microscope micrographs using a linear intercept method.…”
Section: Methodsmentioning
confidence: 83%
“…An MPB is a compositionally configured region separating the components of the solid solution with different orientations of polarization. Among these compositions, xPbTiO 3 -(1-x)BiScO 3 (PT-BS) is a binary system that has received attention due to the elevated piezoelectric properties at/near the MPB region. The phase diagram of PT-BS suggests that when x= 0.64 (0.64PT-0.36BS) the composition is in the vicinity of the MPB region, with coexisting tetragonal and either rhombohedral or monoclinic phases, and showing a high piezoelectric response (d 33 ≅460 pC/N) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric alloy systems exhibiting morphotropic phase boundary (MPB), such as lead-zirconate-titanate (PZT), BiScO3-PbTiO3 (BSPT) are of great scientific and technological importance because of their use as pressor-sensors and actuators [1][2][3][4][5] . Though such piezoelectric materials are being extensively used, the mechanisms leading to the anomalous piezoelectric response is still a subject matter of considerable debate.…”
mentioning
confidence: 99%